The Role of Computerized Applications in Making Village Financial Reports - Vina Arnita; Zuraida Tharo (Universitas 17 Agustus 1945 Semarang, 2024)
Transparent, accountable, and efficient village financial management is an important element in supporting sustainable village development. However, village financial management often faces various challenges, such as limited human resources, technological infrastructure, and the risk of manual errors in preparing financial reports. In an effort to overcome these challenges, the application of computerized applications such as the Village Financial System (Siskeudes) is a relevant solution. This study aims to identify the role of computerized applications in improving the quality of the preparation of village financial reports, reveal the perceived benefits, and explore the constraints and strategies for optimizing implementation. This research uses a descriptive qualitative approach by collecting data through interviews, observations, and document analysis in several villages that have used computerized applications. The results show that the use of computerized applications significantly improves the efficiency of the financial administration process, reduces recording errors, and produces financial reports that are more accurate and in accordance with government accounting standards. In addition, the application supports transparency and accountability of village financial management through easy access to data for stakeholders. Obstacles faced include the low digital literacy of village officials, limited technological infrastructure, and resistance to the application.